Organocatalytic enantioselective direct vinylogous michael addition of alpha,beta-unsaturated gamma-butyrolactam to beta-acyl acrylates and 1,2-diacylethylenes - Chen, Yi-Ru; Das, Utpal; Liu, Meng-Hsien; Lin, Wenwei (Journal of Organic Chemistry, 2015)
A highly efficient Michael addition of alpha,beta-unsaturated gamma-butyrolactam to various beta-acyl acrylates and ene-diones to provide synthetically useful compounds was developed. The products were obtained with high diastereo- and enantioselectivities (up to >25:1 dr and 99% ee) containing adjacent tertiary stereocenters.

Synthesis route to pyrrolones from -cyano ,-unsaturated ketones and -isocyano esters by oxidative dearomatization of 2-aminofuran intermediates - Mahida, Anil K.; Kale, Someshwar B.; Das, Utpal (European Journal of Organic Chemistry, 2017)
An efficient method for the catalyst/promoter-free synthesis of tetrasubstituted furan derivatives proceeding through the [4+1] cycloaddition of isocyanoacetates with electron-deficient olefins was developed. The products were obtained in good to excellent yields without any column chromatography. Oxidative dearomatization of these furans was achieved only in the presence of oxygen, which led to pyrrolones in high yields.

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

1,6-Conjugate-addition-induced [2+1] annulation of para-quinone methides and pyrazolones: synthesis of bis-spiro compounds with contiguous quaternary spiro-centers - Kale, Someshwar B.; Jori, Popat K.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (Organic Letters, 2019)
A diastereoselective formal 1,6-conjugate-addition-mediated [2 + 1] annulation reaction using p-quinone methides and pyrazolones has been described. The corresponding bis-spiro[cyclohexadienone-cyclopropane-pyrazolone] compounds were obtained in very good yield under mild reaction conditions.

Alpha-Angelica lactone in a new role: facile access to N-Aryl tetrahydroisoquinolinones and isoindolinones via organocatalytic alpha-CH2 oxygenation - Thatikonda, Thanusha; Deepake, Siddharth K.; Das, Utpal (Organic Letters, 2019)
A method for the direct oxidation of various N-aryl tetrahydroisoquinolines and isoindolines to the corresponding lactams using alpha-angelica lactone as a catalyst was developed. The utility of the method was further demonstrated by synthesis of indoprofen and indobufen.

Alpha-Angelica lactone catalyzed oxidation of benzylic sp(3) C-H bonds of isochromans and phthalans - Thatikonda, Thanusha; Deepake, Siddharth K.; Kumar, Pawan; Das, Utpal (Organic & Biomolecular Chemistry, 2020)
A metal-free organocatalytic system has been developed for highly efficient benzylic C-H oxygenations of cyclic ethers using oxygen as an oxidant. This oxidation reaction utilizes alpha-angelica lactone as a low cost/low molecular weight catalyst. The optimized reaction conditions allow the synthesis of valued isocoumarins and phthalides from readily available precursors in good yields. Mechanistic studies indicate that the reaction pathway likely involves a radical process via a peroxide intermediate.

Acid mediated sulfonylation of para-quinone methides with tosylmethyl isocyanides for the synthesis of diarylmethyl sulfones - Kumar, Pawan; Kale, Someshwar B.; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2021)
An efficient, hydrochloric acid promoted reaction for the synthesis of diarylmethyl sulfones has been developed via unprecedented 1, 6-conjugate addition reaction of tosylmethyl isocyanide (TosMIC) with para-quinone methides.This catalyst free reaction provides various diarylmethyl sulfones in good to excellent yields in an operationally simple method under metal free conditions. Further transformations of the productsare also demonstrated.
Keywords: 1; 6-Conjugate addition; aromatization; Diarylmethylsulfone; para-Quinonemethide; TosMIC

Alpha-angelica lactone catalyzed oxidation of pyrrolidines to lactams - Deepake, Siddharth K.; Kumar, Manish; Kumar, Pawan; Das, Utpal (European Journal of Organic Chemistry, 2022)
Herein, we report an efficient protocol for the synthesis of gamma-lactams from pyrrolidines and oxygen. The strategy follows a two-step process involving an initial generation alpha-amino alkyl radicals from pyrrolidines and oxygen in presence of 4-dimethylaminopyridine (DMAP) followed by trapping of the radical with oxygen species. This protocol demonstrates good functional group acceptance and provides a direct method to access gamma-lactams. The lactam derivatives were obtained in up to 98 % yield.
Keywords: alpha-Amino alkyl radicals; alpha-Angelica lactone; lactams; Oxidation; Pyrrolidines

Rongalite as a sulfone source: sulfonylation of para-quinone methides and alkyl/allyl halides - Kale, Someshwar B.; Jori, Popat K.; Das, Utpal (Chemistry-an Asian Journal, 2022)
A one-pot three-component reaction using p-quinone methides, rongalite and alkyl/allyl halides has been described. The corresponding unsymmetrical sulfones were obtained in good yields under mild reaction conditions in the absence of any metal, base or any other additive.
Keywords: Alkyl halides; diaryl methine; p-Quinone methide; rongalite; sulfonylation

Radical cascade cyclization of unactivated alkene-tethered indoles with aryldiazonium salt and sodium metabisulfite to access Azo- and Sulfonylated-2,3-Dihyro-1H-pyrrolo[1,2-a]indoles - Kumar, Pawan; Rai, Archana; Kumar, Manish; Krishna, Gamidi Rama; Das, Utpal (Journal of Organic Chemistry, 2023)
A method for the construction ofheterocyclic scaffold2,3-dihyro-1H-pyrrolo[1,2-a]indolesvia arylsulfonylradical-triggered cascade cyclization of unactivated alkene-tetheredindoles in the absence of any external photocatalyst has been developed.This protocol features easily accessible starting materials such assodium metabisulfite and aryldiazonium tetrafluoroborates at roomtemperature and offers good functional group compatibility, enablingthe introduction of various functionalized sulfonyl and azo groupsinto pyrrolo[1,2-a]indoles.

Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.

Accessing meta -enone-substituted anisoles using ArN 2 BF 4 as precatalyst via rearrangement of alkyne-tethered cyclohexadienones - Rai, Archana; Das, Utpal (Synthesis-Stuttgart, 2024)
Keywords: alkyne-tethered cyclohexadienone; diazonium salt; rearrangement; substituted anisoles

Reaction of 4 (Alkynyloxy)cyclohexa-2,5-dienones with Dimethyl Sulfoxide: a catalyst-free formation of 6/5/3-fused tricyclic enones - Rai, Archana; Das, Utpal (Journal of Organic Chemistry, 2024)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">6/5/3-Fused tricyclic enones were obtained when 4-(alkynyloxy)cyclohexa-2,5-dienones were treated with DMSO at 150 °C. The reaction proceeded via a four-membered oxathietene intermediate. The protocol developed is atom economical, has a broad substrate scope, and is amenable to gram-scale synthesis. The products obtained are susceptible to further synthetic transformations.

Rongalite as a C1 source: sulfonylmethylation of indoles with aryl/alkyl hydrazides and sulfinates - Kale, Someshwar B.; Patil, Tejaswini A.; Das, Utpal (Journal of Organic Chemistry, 2024)
Herein, we present a sulfonylmethylation of indoles with aryl/alkyl hydrazides and sulfinates that provides viable access to sulfone compounds using rongalite as a C1 source. This protocol features readily available chemicals and simple operations, and the products were obtained in moderate to good yields.

Ipso-cyclization via a dienone-phenol rearrangement of alkynyloxy cyclohexadienones for the synthesis of oxaspiro[4.5]trienones - Rai, Archana; Kundu, Ananya I.; Shukla, Ekta; Das, Utpal (Journal of Organic Chemistry, 2025)
Herein, we present a convenient method to access oxaspiro[4.5]trienone compounds from alkynyloxy cyclohexadienones. The reactions are catalyzed by Lewis/Bronsted acids, yielding the desired products in moderate to good yields under very mild reaction conditions. The process, which involves a dienone-phenol rearrangement, is characterized by its simplicity and the absence of any additional activators. The synthesis of the oxaspiro[4.5]trienone compounds is amenable to gram-scale reactions along with subsequent product transformations, making this approach practical and attractive.

Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.

Photocatalytic oxidation of α-substituted amines to lactams/amides - Kumar, Manish; Kumar, Pawan; Das, Utpal (Advanced Synthesis & Catalysis, 2025)
We, herein, report a base free, photocatalytic decyanation of alpha-aminonitriles. A range of amides and lactams were obtained in 52-95% yields. Control experiments indicate O2 as an amide/lactam oxygen source and the reaction (lactam formation) follows radical pathway via dioxetanimine species. This methodology also applied for alpha-ester/aldehyde substituted pyrrolidines in the presence of a base, probably via decarboxylation pathway.
Keywords: alpha-Aminonitriles; Decyanation; Dioxetanimine; Photocatalytic; pyrrolidine

Synthesis of benzannulated [5,6] oxa-fused/spiro-lactones via [4+2] cycloaddition with quinone methides: new insights into deconjugated butenolide reactivity - Kumar, Manish; Kale, Someshwar B.; Jawahar, Subramani; Barkade, Apurva D.; Das, Utpal (Journal of Organic Chemistry, 2025)
In this study, we unfold a Lewis-acid-catalyzed inverse electron demand hetero Diels-Alder (IEDHDA) [4 + 2] reaction, leveraging the unique beta-selective nucleophilicity of deconjugate lactone in conjunction with quinone methides for the synthesis of polycyclic fused and spiro acetals in a one-pot process. This cascade annulation reaction efficiently generates 3/4 chiral centers with high diastereoselectivity. The developed methodology proceeds under mild reaction conditions and exhibits a broad substrate scope for fused and spiro acetal formation.